Competition in Infrastructure Investment Among Canadian Provinces - Djukic, Sonja (Université d'Ottawa | University of Ottawa, 2007)
This paper evaluates the importance of the interaction between provincial governments on infrastructure spending. In addition to the interdependence between the provinces in infrastructure investments, the role of federal grants, demographics and urbaniza